REASONABLE TIME AS A PRINCIPLE OF CRIMINAL PROCEDURE - Dilbandyan, Samvel (State and Law, 2025)
This article is devoted to several issues of theoretical and practical application of the principle of “Reasonable Time of Criminal Proceedings”. The mentioned principle was enshrined in the current Code of Criminal Procedure for the first time and has not yet been sufficiently studied in the domestic procedural literature. In addition, in practice, it is often violated due to objective or subjective factors, which naturally gives rise to serious concern. Today, there are numerous cases when judges are subject to disciplinary liability for the fact of violation of a reasonable time in the proceedings they are examining. It is worth noting that the public is quite negatively disposed towards cases of prolonged examination of criminal cases. The fact that the prolonged examination of criminal cases leads to the expiration of the statute of limitations for bringing a person to criminal liability provided for by the Criminal Code, as a result of which persons who have committed a crime are released from criminal liability, is even more unacceptable. This circumstance belittles the role of justice among the public. Of course, there are also problems that are objective obstacles to the implementation of criminal proceedings within a reasonable time. In particular, the lack of deadlines for conducting preliminary investigations before initiating criminal prosecution, the lengthy implementation of expert examinations, as well as the failure of participants in the proceedings to appear at the trial are problematic. Therefore, it is important to provide guarantees that should ensure the possibility of conducting proceedings within a reasonable time.
Keywords: criminal proceedings; principles of criminal proceedings; criminal prosecution; pre-trial proceedings; trial; reasonable time; criteria for a reasonable time; violation of a reasonable time